Effect of GDF11 on proliferation and apoptosis of esophageal cancer cells - Gu, Biao; Wang, Qi; Dai, Weijie; Ma, Gang; Song, Yaqi; Wu, Qingquan (Cellular and Molecular Biology, 2018)
This study was aimed at investigating the effect of growth differentiation factor 11 (GDF11) on the proliferation and apoptosis of esophageal cancer cells. Serum levels of GDF11 in esophageal cancer patients were determined with ELISA kits, and the correlation between serum GDF11 and pathological features of esophageal cancer were determined. The effect of recombinant GDF11 on the growth of esophageal cancer cells was measured by CCK6 method. In order to investigate the effect of recombinant GDF11 on the proliferation and apoptosis of esophageal cancer cells, the expression of apoptosis-promoting protein Bax and proliferative-associated protein Bcl-2 in esophageal cancer cells were determined using western blot. Moreover, GDF11 was used to treat esophageal cancer cells, and its effect on proliferation and apoptosis was determined with MTT assay and flow cytometry, respectively. The serum content of GDF11 was much less in esophageal cancer patients than in the control group. Esophageal GDF II in cancer patients was correlated with cancer differentiation: the higher the degree of differentiation, the higher the content of GDF11. GDF11 inhibits proliferation and apoptosis of esophageal cancer cells.